Association between COVID-19 vaccination and coronary heart disease: based on 2023 national health interview survey data - Mao, Juncong; Hong, Yunfei; Bao, Rui (Frontiers in Public Health, 2025)
BackgroundCoronary heart disease (CHD) represents a critical cardiovascular ailment necessitating thorough investigation. This research endeavors to explore the potential link between COVID-19 vaccination and CHD, using data from the National Health Interview Survey (NHIS).MethodsThe study encompasses 20,906 participants from the 2023 NHIS cohort, and these participants were stratified into two groups: CHD patients and non-CHD individuals (controls). To determine the protective factors for CHD, both univariate and multivariate logistic regression analyses were carried out. Furthermore, Receiver Operating Characteristic (ROC) curves were plotted to assess the predictive performance of models that consider COVID-19 vaccination as a potential protective factor against CHD.ResultsIn this study, a number of potential risk factors were investigated, including age (AGEP_A), sex (SEX_A), and race (RACEALLP_A) et al. Among them, the number of COVID-19 vaccinations was confirmed to be an effective protective factor for preventing coronary heart disease. Univariate logistic regression analysis showed that the risk of coronary heart disease was reduced in people who received 2 doses (OR = 0.68, 95% CI 0.49–0.92, p = 0.016), 3 doses (OR = 0.47, 95% CI 0.34–0.63, p < 0.001), 4 doses (OR = 0.39, 95% CI 0.28–0.53, p < 0.001), 5 doses (OR = 0.31, 95% CI 0.22–0.43, p < 0.001), and 6 or more doses (OR = 0.21, 95% CI 0.14–0.32, p < 0.001) of the COVID-19 vaccine. In the multivariate logistic regression analysis, Model 3 (after adjusting for multiple covariates) showed that the OR for those who received 6 or more doses of the vaccine was 0.459 (95% CI 0.289–0.726, p < 0.001). Receiver Operating Characteristic (ROC) curve analysis showed that the AUC for predicting coronary heart disease based on COVID-19 vaccination status was 0.845 (95% CI 0.8357–0.8539).ConclusionBased on NHIS database, a predictive model for CHD has been developed, and COVID-19 vaccinations were identified as a protective factor against CHD. This model holds potential clinical value.